PENGARUH JALAN KAKI TERHADAP KETIDAKSTABILAN GLUKOSA DARAH PADA PASIEN DIABETES MELLITUS TIPE 2 - Nina Fentiana; Ika Ariyanti; Erita Gustina; Handerman Vitu Gea; Kayla Azuri Faradiba (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Diabetes mellitus is a chronic non-communicable disease whose incidence continues to increase globally. This disease occurs due to insufficient insulin production or insulin does not work effectively, making blood glucose levels difficult to control. The purpose of this study was to determine whether physical walking can stabilize blood glucose in type II diabetes mellitus patients at Putri Hijau Class II Hospital, Medan. This study used a quasi-experimental study with a control group. The sampling technique used was a purposive sampling technique so that the number of samples obtained according to the inclusion criteria was 40 participants who were divided into two groups: 20 participants in the intervention group and 20 participants in the control group. Based on the Wilcoxon test, there was a significant effect p <0.000. The results of the study showed that physical activity intervention walking can stabilize blood sugar levels in type II diabetes mellitus patients. It can be concluded that doing walking regularly can stabilize blood glucose. Suggestions are expected for type II diabetes mellitus patients to apply walking as a non-pharmacological therapy. It is hoped that it can be a complementary therapy for type II diabetes mellitus sufferers who are treated in hospital or at home